COOPERATIVE INTEGRATED READING AND COMPOSITION TECHNIQUE: (A Mean Of Improving Students’ability In Writing Explanation Text) - Hijjatul Qamariah; Rosdina; Nostaria Fitri (English Education Department, 2019)
The objective of this study was to find out Cooperative Integrated Reading and Composition technique to improve the students’ writing ability in explanation text and to find out the students’ perceptions about using CIRC technique in writing explanation text at second graded of SMAN 5 Banda Aceh. In this research, there was one class taken which consist of 30 students that deveded in 6 groups. The data was obtained from the students’ test sheet. The data are collected by using quantitative design through pre test and post test. The mean score of post-test was 77,16 and the mean score of pre-test was 63,33. It means that the mean score of post-test is higher than mean score of pre-test. Afterward, those scores were used to determine t-score, which the result of t-score is 11, 15. In addition, t-table at the significance level of 0,05 is 2,01505. The result showed that t-score is higher than t-table. Ho Rejected and Ha Accepted if t-score more than t-.Table Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that there was improvement of students’ writing ability in explanation text after using CIRC technique.